A compreensão do ethos diante de normas morais e religiosas - Pereira, João Nogueira (Horizonte, 2005)
This article focuses on the relation between ethics and religious practice and experience. The presence of ethics is not restricted to the wide scope of Semitic tradition or prophetic religions, but reaches the roots of mystical and sapient religiosity. The text aims at understanding that relation in depth, in what concerns the codes and norms of various religions, as well as the religious practice of communities. Ethics plays a fundamental role as a science of ethos. The article also comprises some terminological and semantic distinctions between the terms ‘ethics’ and ‘morals’. Within the religious universe, the fundamental place of ethics is investigated through the rationality of moral values of the main world religions.